Educational Disruption in Arabic Language Learning (Psycholinguistic Perspective) - Salma Lulu Maknuna; Ahmad Zaki Alhafidz; Agung Setiyawan (Universitas Ahmad Dahlan, 2023)
Technology that continues to develop causes disruption in various fields of life, including in the field of Arabic education and learning. Traditional learning, which is starting to be replaced with technology-based and online learning systems, must be adapted and maximized immediately in order to realize effective learning. This phenomenon also needs to be considered from a psycholinguistic perspective, which has an important role in language learning. This literature research aims to describe how learning Arabic is in the current era of educational disruption and how it is viewed from a psycholinguistic perspective. Some examples of learning Arabic in this era of educational disruption are as follows: 1) Online Learning. 2) Educational Applications. 3) Project Based Learning. 4) Game-Based Learning 5) VR-Based Learning (Virtual Reality). Among the theories related to learning Arabic in this era of educational disruption are as follows: Information Processing Theory, Language Skills Theory, Collaborative Learning Theory. Constructivism Theory and Theory of Multiple Intelligences. A psycholinguistic perspective can provide several views that must be considered in viewing educational disruption from face-to-face learning to digital learning. Several aspects that can be considered in this perspective are: 1) Language skills, 2) Social interaction, 3) Student involvement, 4) Information processing, 5) Assessment.